Nitrogen rates and plant density interactions enhance radiation interception, yield, and nitrogen use efficiencies of maize - Tian, Peiyu; Liu, Jiamin; Zhao, Yanan; Huang, Yufang; Lian, Yanhao; Wang, Yang; Ye, Youliang (Frontiers in Plant Science, 2022)
The contributions of the different leaf layers to maize yields identified as middle leaf > lower leaf > upper leaf, where the vertical photosynthetically active radiation (PAR) in the canopy gradually decreases. We hypothesized that the allocation of more PAR and nitrogen (N) to the highest contributing leaves will would be beneficial for higher yields and N use efficiencies. The N application rate and plant density effectively regulated the canopy light and N distribution. We evaluated the interactive effects of N rate and plant density on the agronomic and ecophysiological characteristics of leaves at different orientations in a 2019/2020 field experiment. In this study, an N application rate of 180 kg ha–1 coupled with a plant density of 82,500 plants ha–1 achieved the highest yield and N recovery efficiency (NRE). In contrast to the traditional farming practices in northern China, the density was increased and N rate was reduced. Densification from 52,500 to 82,500 plants ha–1 increased the population leaf area index (LAI) by 37.1% and total photosynthetically active radiation (TPAR) by 29.2%; however, excessive density (from 82,500 to 97,500 plants ha–1) drastically reduced the proportion of TPAR by 28.0% in the lower leaves. With increased density, the leaf areas and angles of the upper leaves decreased much more than those of the other leaves, which allowed the middle and lower leaves to access more light, which manifested a smaller extinction coefficient for light (KL). A high yield (>1,000 kg ha–1) of maize could be achieved simultaneously with higher NRE; however, it was negatively correlated with internal N use efficiency (IEN). Higher N concentrations and lower total performance index (PItotal) in the lower leaves may be an important rationale for the reduction of IEN in high-yielding maize. Additionally, decreased N rate without yield reduction under higher densities was primarily attributed to the more uniform vertical N distribution [a smaller extinction coefficient for N (KN)]. These results suggest that the N fertilizer rate can be moderately reduced without a reduction in maize yield under high plant densities in northern China.